Islam and Impact of News Reporting: Between Religious Activities and Health Protection - Nasution, Nadya Amalia; Khomsahrial Romli (Jurnal Komunikasi Islam, 2023)
Islamic religious activities that are bound together, such as congregational prayers, recitations, and da’wah activities, are some of the things that must be canceled when Covid-19 hits. The decline in social activity, interaction, and public trust is closely related to the increasingly rapid flow of information from various media channels. This research tries to uncover the news about Covid-19 in the mass media in influencing the behavior of the Bandar Lampung community religious activities. The research method used is explanatory quantitative of 422 respondents, obtained by accidental sampling technique. The findings illustrate that there has been an effect of the mass media coverage toward the attitude of the people of Bandar Lampung City, particularly regarding religious activities (35.04%). It has also revealed that the religious community was in a dilemma of choosing between health protection and religious behavior suit to shari’a.